PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN INFORMATIKA KELAS VII DENGAN METODE RESEARCH AND DEVELOPMENT (R&D) - Mahmudin, Nurman Sah; Saprudin, Usep (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Currently computer science subjects are still relatively new and are still being introduced in some drive schools, so it is important for students to learn them, especially before students at the previous level (elementary school) take computer science subjects, I find it difficult to learn it. In the Industrial 4.0 era, computer science subjects must be studied from an early age. Therefore, researchers developed interactive multimedia learning media to facilitate learning and motivate students to engage more specifically with computer thinking materials. The concept of interactive learning media is more than just a focus on the material. The researcher added audio, visual video, animation, and what students could try out later. Researchers made the media using Adobe Flash CS6 software. “The design method used is research and development, passing through four stages: preliminary research, planning, design, and development. The results of the study meet the categories of efficacy, validity and practical relevance given and increase students' understanding in the high category